Productive University, Global and Regional Experiences and Trends: An Analytical Study - Al-Herbawi, Fatima Fayez (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to define the concept of productive university. He presented models and fields of work. And know the justifications for the transformation of producing universities. Develop a suggested vision for a shift towards a productive university. The results have shown that the productive university contributes to contributing to reducing unemployment and providing trained, skilled national cadres. And achieve the requirements of continuous and sustainable development of the economy. And that there are sources of strength in our Arab world that enable universities to move towards a productive university model. Such as: constitutions, laws, political decisions, and international pressure that drive the shift towards a model of a productive university. The study recommended a set of recommendations, the most important of which are: - Reconsidering the process of preparing students in light of the changes that we live in our rapidly changing world and developments. - Opening windows and channels between the university and the community to find out about its contemporary issues and problems.